2016
DOI: 10.15605/jafes.031.02.09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sensorineural Hearing Loss and its Association with Glycemic Control in Filipino Patients with Diabetes at the Philippine General Hospital

Abstract: Background. Sensorineural hearing loss (SNHL) is a form of diabetic neuropathy. Its prevalence rate varies from 21.7-73.3% among different populations. The association of this complication with long-term glycemic control has not been described extensively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…Of the n=310 diabetics enrolled in this study to determine the prevalence of SNHL in DM, a high prevalence of 46.1% (n=143) was noted. Similarly, a comparable prevalence of 43.6% has been reported by Pemmaiah & Srinivas [5], 45% by Mozaffari M et al in an Iranian study [9], and 45.31% by Gutierrez J et al [10] A much higher prevalence of 67.5% has been reported by Ren H et al [11] and 51.3% by Rajamani S et al [12] Horikawa et al [13], and Meena R et al [14] also reported a higher prevalence of HL in DM. A very low prevalence of 14.3% was reported by Trevi˜no-González et al [15] Kim et al reported in a cohort study that the incidence rate of HL in sample population with normal glucose levels and those with DM were 1.8 and 9.2 per 1000 person-years, respectively [16].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Of the n=310 diabetics enrolled in this study to determine the prevalence of SNHL in DM, a high prevalence of 46.1% (n=143) was noted. Similarly, a comparable prevalence of 43.6% has been reported by Pemmaiah & Srinivas [5], 45% by Mozaffari M et al in an Iranian study [9], and 45.31% by Gutierrez J et al [10] A much higher prevalence of 67.5% has been reported by Ren H et al [11] and 51.3% by Rajamani S et al [12] Horikawa et al [13], and Meena R et al [14] also reported a higher prevalence of HL in DM. A very low prevalence of 14.3% was reported by Trevi˜no-González et al [15] Kim et al reported in a cohort study that the incidence rate of HL in sample population with normal glucose levels and those with DM were 1.8 and 9.2 per 1000 person-years, respectively [16].…”
Section: Discussionsupporting
confidence: 76%
“…In current study prevalence of HL in males was 65.03% while in females it was 34.97% with a male to female ratio of 1.86:1, while Gutierrez J et al found no significant in SNHL gender wise with 48.94% males and 43.21% females [10]. The higher prevalence in males in this study could be due to the fact that only a small minority of female go out for work, compared to males resulting in lesser stress and HTN in females.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Although the findings of studies focusing on the relationship between hearing acuity and the degree of hyperglycemia by diabetes type are conflicting, 5 several risk factors have been identified as being associated with hearing loss in diabetes patients. 6 This study aimed to assess the prevalence of hearing loss and its severity among patients with type 2 diabetes in a tertiary diabetes center. The second aim of this study was to evaluate the factors associated with hearing loss.…”
Section: Introductionmentioning
confidence: 99%